Blood-Derived Products for Tissue Repair/Regeneration - Maffulli, Nicola; Andia, Isabel (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue on (3z(BBlood-Derived Products for Tissue Repair and Regeneration(3y (Breveals the evolution and diversity of platelet rich plasma (PRP) technologies, which includes experimental research on novel formulations, the creation of combination therapies, and the exploration of potential modifiers of PRPs, as well as efficacy of PRP therapies in clinical veterinary and human applications. Scientist and clinicians are now starting to develop different treatments based on their reinterpretation of the traditional roles of platelets and plasma, and the current Issue has provided a forum for sharing research and ways of understanding the associated medicinal benefits from different points of view. The research interest in this area has covered different medical disciplines, such as ophthalmology, dentistry, orthopedics, and sports medicine.s
English
Keywords: n/a; biomaterial; redifferentiation; regenerative medicine; skeletal muscle regeneration; furcation defects; Platelet-Rich Plasma (PRP); PRP; fracture; fibrin sealant; periodontal surgery; bone regeneration; serum derived from plasma rich in growth factors (s-PRGF); cartilage repair; myofibroblasts; autologous platelet concentrates; burns; satellite cells; articular cartilage; stem cell niche; wound healing; quantification; growth factors; biologics; platelet rich plasma; meniscus; adipose tissue; Carprofen; platelet-rich fibrin; platelets; hyperacute serum; bone defects; serum eye drops; corneal epithelial defect; fibrosis; dog; myoblasts; differentiation; chronic meniscal lesion; horizontal meniscal tear; PRGF; collagen hydrogels; periodontal defects; bone grafting material; composition; cell therapy; bone healing; tissue healing; trephination; plasma rich plasma (PRP); bone repair; plasma rich in growth factors; knee arthrosis; meniscus tear; cornea regeneration; wrist osteoarthritis; periosteal sheet; Platelet-Poor Plasma (PPP); platelet-rich plasma; microfat